Diseño de un túnel de viento, con monitoreo por telemetría, para pruebas de estructuras de ingeniería y arquitectura (2017)
A wind tunnel is an equipment that allows to perform analysis of the behavior of an object against a wind current at a given speed; This study requires conditions of geometric similarity, kinetic similarity and dynamic similarity. For the development of the project a selection of seven wind tunnels focused on aerodynamics and architecture was carried out in order to characterize the current situation of the wind tunnels in Colombia and mainly in the application to architecture and to determine how the tunnel proposed for the Fundación Universidad de América in front of the others. In order to determine the total size and power required by the wind tunnel to meet the design conditions, the losses generated by the variable cross-section geometry in the tunnel and its different components were calculated in order to determine the Fan power required to guarantee the desired speed in the test chamber at the installation site that is Bogotá DC For the validation of the design, the OpemFoam software and the rhoCentralFoam solver were used for compressible flow and to determine the behavior of the fluid in the tunnel.